The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1093/aobpla/pls021
|View full text |Cite
|
Sign up to set email alerts
|

Real-time analysis of sulfur-containing volatiles in Brassica plants infested with root-feeding Delia radicum larvae using proton-transfer reaction mass spectrometry

Abstract: Proton Transfer Reaction-Mass Spectrometry (PTR-MS) analyses revealed that damaged Brassica roots emit sulfur-containing volatiles. B. nigra, B. juncea and B. napus emitted isothiocyanate markers, whereas B. rapa, B. oleracea, and B. carinata emitted methanethiol. These compounds can be used as markers for root damage by insect larvae and other below-ground herbivores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 49 publications
5
33
0
Order By: Relevance
“…Of particular relevance is the finding that the changing profile of organosulfur exudates that occurs in Brassica spp. roots in response to herbivore attack or a tissue breach can be monitored in real time by proton transfer reaction-mass spectrometry (Crespo et al, 2012;Danner et al, 2012;van Dam et al, 2012;Samudrala et al, 2015). If conventional metabolome analysis sample preparation methods had been used in these cases (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular relevance is the finding that the changing profile of organosulfur exudates that occurs in Brassica spp. roots in response to herbivore attack or a tissue breach can be monitored in real time by proton transfer reaction-mass spectrometry (Crespo et al, 2012;Danner et al, 2012;van Dam et al, 2012;Samudrala et al, 2015). If conventional metabolome analysis sample preparation methods had been used in these cases (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Published studies found that in Brassica species, the enzymatic thiol methyltransferase (TMT) have a strong influence on the hydrolysis of GS products to volatile sulfides (e.g., DMDS and dimethyl trisulfide (DMTS)) (Attieh et al, 2002;van Dam et al, 2012). It is reported that the artificial and natural damage to B. napus (L.) and B. juncea (L.) roots led to highest TMT activities in their leaves (van Dam et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that the artificial and natural damage to B. napus (L.) and B. juncea (L.) roots led to highest TMT activities in their leaves (van Dam et al, 2012). Existing data indicate that the physical conditions and herbivorous insects are extremely potent in the release of sulfur volatiles (Dugravot et al, 2005;Rouseff et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This verifies the need to optimize the settings of the instrument before the start of the plant experiments. Further details and explanation about the biological background of the experiments can be found in van Dam et al [8].…”
Section: Plant Emissionsmentioning
confidence: 99%
“…The latter makes possible real time analysis and simultaneous monitoring of several volatile compounds. Owing to these advantages compounds that are typical of Brassicaceae family species [8]. Glucosinolates are non-volatile compounds.…”
Section: Introductionmentioning
confidence: 99%